2019
DOI: 10.1371/journal.pone.0214158
|View full text |Cite
|
Sign up to set email alerts
|

Heart ventricular histology and microvasculature together with aortic histology and elastic lamellar structure: A comparison of a novel dual-purpose to a broiler chicken line

Abstract: The use of dual-purpose chickens is a strategy to avoid killing one-day-old male chicks of egg laying lines. Lohmann Dual (LD) is a novel dual-purpose chicken line created by the crossbreeding of layer and broiler lines. However, many of the cardiovascular diseases of broilers are likely to be associated with intensive genetic selection for growth and feed conversion efficiency. This study aimed to compare the macroscopic and microscopic structure of the heart and the aorta of the LD chicken line with that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…The tibiotarsal bones of male chicks from two different lines, a dual-purpose line (Lohmann Dual, LD) and a broiler line (Ross 308) were used for this study. The same chickens had previously been used to investigate the gastrointestinal tract [4] as well as the heart and aorta [3]. Animals and husbandry conditions were described in detail in the above studies [3,4].…”
Section: Animals and Husbandrymentioning
confidence: 99%
See 3 more Smart Citations
“…The tibiotarsal bones of male chicks from two different lines, a dual-purpose line (Lohmann Dual, LD) and a broiler line (Ross 308) were used for this study. The same chickens had previously been used to investigate the gastrointestinal tract [4] as well as the heart and aorta [3]. Animals and husbandry conditions were described in detail in the above studies [3,4].…”
Section: Animals and Husbandrymentioning
confidence: 99%
“…The same chickens had previously been used to investigate the gastrointestinal tract [4] as well as the heart and aorta [3]. Animals and husbandry conditions were described in detail in the above studies [3,4]. Briefly, the chickens were reared under similar husbandry conditions until they reached a body weight (BW) of 2000 g, i. e. 35 days for Ross chickens and 63 days for LD chickens.…”
Section: Animals and Husbandrymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have clearly demonstrated that the use of dual-purpose genotypes is associated with compromises of both egg and meat production (7)(8)(9). Despite the lower performance of dual-purpose genotypes as compared to specialized layer or meat-type genotypes, their implementation in farming systems might nevertheless contribute to the mitigation of high-performance associated health and welfare problems in both broilers and laying hens (10,11). Furthermore, dualpurpose genotypes may need lower protein levels in their diets, implying a smaller dependency on the highly nutrient dense diets for high performance birds (12,13).…”
Section: Introductionmentioning
confidence: 99%